Pengaruh Variasi Konsentrasi Bakteri Bacillus Subtilis Terhadap Sifat Mekanik Beton Di Lingkungan Sulfat - Ahmad Zulfitri; Iskandar Romey Sitompul; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Concrete has several advantages and disadvantages. One of the weaknesses of concrete is crack. The strength of concrete will decrease if there are cracks. One of the innovations that can overcome the problem is by using bacteria as a concrete mixture material. One way to overcome cracks in concrete is to add Bacillus subtilis bacteria. Bacillus subtilis bacteria is able to repair cracks in concrete. This study used concrete with a mixture of Bacillus subtilis bacteria with variations in the volume of different concentrations namely 105 cells/20 ml, 105 cells/25 ml and 105 cells/30 ml. Bacterial concrete soaked in the sulfate solution. This study examined the mechanical properties of concrete, namely compressive strength and flexural strength. Testing is carried out at the concrete age of 28 days and 56 days after soaking the sulfate solution. Based on the results of the study obtained that the volume of the best concentration of Bacillus subtilis bacteria on concrete is 105 cells / 20 ml, with the highest compressive strength test results with an increase of 28.16% and 22.94% against normal concrete at the time of testing at the age of 28 and 56 days, the highest flexural strength test results with an increase of 11.83% and 14.74% against normal concrete at the time of testing were 28 and 56 days old in the sulfate environment.Keyword : cracks, Bacillus subtilis, sulfate, compressive strength, flexural strength